2017
DOI: 10.4102/jamba.v9i1.326
|View full text |Cite
|
Sign up to set email alerts
|

Assessing social vulnerability to drought in South Africa: Policy implication for drought risk reduction

Abstract: The aim of this article was to assess and identify social vulnerability of communal farmers to drought in the O.R. Tambo district in the Eastern Cape province of South Africa using a survey data and social vulnerability index (SoVI). Eleven social vulnerability indicators were identified using Bogardi, Birkman and Cardona conceptual framework. The result found that an SoVI estimated for O.R. Tambo district was very high with a Likert scale of 5 for cultural values and practices, security or safety, social netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…Of concern was that a high percentage of consumers had an education level below grade 9, which is the minimum school education level in South Africa [25]. This result is similar to that of other reports in Alfred Nzo, where 58% of respondents were without formal education [26] and OR Tambo had 26% with no schooling at all [27]. It has been reported that a low level of education exacerbates a high unemployment rate [25,28,29], and this may impact negatively on public health initiatives targeted to improve consumers knowledge and practices on consumption of safe pork [30].…”
Section: Discussionsupporting
confidence: 79%
“…Of concern was that a high percentage of consumers had an education level below grade 9, which is the minimum school education level in South Africa [25]. This result is similar to that of other reports in Alfred Nzo, where 58% of respondents were without formal education [26] and OR Tambo had 26% with no schooling at all [27]. It has been reported that a low level of education exacerbates a high unemployment rate [25,28,29], and this may impact negatively on public health initiatives targeted to improve consumers knowledge and practices on consumption of safe pork [30].…”
Section: Discussionsupporting
confidence: 79%
“…For example, Raphael et al (2009) found that the odds of perceived drought being very likely to continue, were significantly higher in women than in men when considering the concern for self or family. Similarly, some studies found that as a demographic characteristic, gender had a critical influence in decisions on drought and agricultural activities (Bahta et al, 2016;Muyambo et al, 2017). The results confirm that animal production is a male dominated career in the studied area, with very little youth involvement.…”
Section: Discussionsupporting
confidence: 71%
“…Equal weights were assigned to indicators to calculate S 0 VI. It has been argued by Cutter et al (2003) and Muyambo (2017) that there is no theoretical basis for assigning different weights to indicate different levels of significance to individual factors' contribution to social vulnerability. The indices were then summed up and divided by the total number of indicators to obtain the SoVI for the five geopolitical zones of Missouri State (see Table 3).…”
Section: Methodsmentioning
confidence: 99%